(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This case series details the management of three teeth with a history of trauma. All the three teeth had an open apex and were disinfected with Triple antibiotic paste /calcium hydroxide – iodoform paste prior to gaining an apical seal with an MTA plug and a definitive coronal seal. Bleaching, veneers, and full coverage crowns were used to restore the affected tooth to their original form and function. The cases were followed for a period of more than one year, to ascertain continued healing of lesion, apical root development, and non-recurrence of further symptoms. This case report intense to highlight the usage of good infection protocols and several restorative techniques to successfully manage the patient. It also highlights a strict adherence to clinical protocol, along with a good standard of care, leading to a successful outcome.